Preclinical retinal neurodegeneration in a model of multiple wclerosis - Fairless, Richard; Williams-Fairless, Sarah K.; Stojic, Aleksandar; Diem, Ricarda (The journal of neuroscience, 2012)
Neurodegeneration plays a major role in multiple sclerosis (MS), in which it is thought to be the main determinant of permanent disability. However, the relationship between the immune response and the onset of neurodegeneration is still a matter of debate. Moreover, recent findings in MS patients raised the question of whether primary neurodegenerative changes can occur in the retina independent of optic nerve inflammation. Using a rat model of MS that frequently leads to optic neuritis, we have investigated the interconnection between neurodegenerative and inflammatory changes in the retina and the optic nerves with special focus on preclinical disease stages. We report that, before manifestation of optic neuritis, characterized by inflammatory infiltration and demyelination of the optic nerve, degeneration of retinal ganglion cell bodies had already begun and ultrastructural signs of axon degeneration could be detected. In addition, we observed an early activation of resident microglia in the retina. In the optic nerve, the highest density of activated microglia was found within the optic nerve head. In parallel, localized breakdown in the integrity of the blood-retinal barrier and aberrations in the organization of the blood-brain barrier marker aquaporin-4 in the optic nerves were observed during the preclinical phase, before onset of optic neuritis. From these findings, we conclude that early and subtle inflammatory changes in the retina and/or the optic nerve head reminiscent of those suggested for preclinical MS lesions may initiate the process of neurodegeneration in the retina before major histopathological signs of MS become manifest.